Telework and women’s perceptions on the right to disconnect: An exploratory study in Portugal - Rebelo, G.; Delaunay, C.; Diamantino, M. F.; Almeida, A. R. (Administrative Sciences, 2024)
Working in the digital age requires a discussion on the right to disconnect. Although it has previously been studied in association with the digital transition movement, the “right to disconnect” has gained relevance in a context of mandatory teleworking due to the COVID-19 pandemic. This situation has led some countries to legislate on the subject, notably Portugal, where the right to disconnect has been enshrined in labour legislation since law no. 83/2021 of 6 December. This article presents a framework of the literature on the right to disconnect, as well as a documentary analysis and an exploratory study carried out in Portugal in November and December 2021, during the COVID-19 pandemic. The survey sought to assess the working conditions of women in telework, particularly about working time. This study stresses that the right to disconnect is linked to the organisation of working time and analyses the negative impact of technology on work, in particular the permanence of the electronic connection to work. The results show that the majority of women value teleworking because they have more time for themselves and their families. However, the women who consider that they have less availability for teleworking indicate that the main reason for this is not being able to disconnect from work. In the context of the digital transition and the expansion of teleworking in organisations and the generalisation of hybrid work, the study of this new “right to disconnect” becomes crucial.